2021
DOI: 10.1111/jvs.12999
|View full text |Cite
|
Sign up to set email alerts
|

Functional biogeography of weeds reveals how anthropogenic management blurs trait–climate relationships

Abstract: Questions: Studies in functional biogeography have mostly focused on unmanaged ecosystems, and neglected testing how management intensity affects communitylevel response of plant traits to bioclimatic gradients. We hypothesize that traitclimate relationships for arable weeds spontaneously establishing in croplands subject to intensive management should differ from the relationships characterizing less intensively managed grassland ecosystems. Location: France.Methods: We computed community-weighted means (CWM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 83 publications
(132 reference statements)
0
7
0
Order By: Relevance
“…This suggests that in absence of strong filtering factors such as competition or disturbances, climate has a higher filtering effect on weed assemblages. Indeed, a recent study investigating traitclimate relationships in plant assemblages revealed that these relationships were much weaker in croplands compared to grasslands, suggesting a reduced sensitivity of plant assemblages to bioclimatic variations in intensively managed habitats [44].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that in absence of strong filtering factors such as competition or disturbances, climate has a higher filtering effect on weed assemblages. Indeed, a recent study investigating traitclimate relationships in plant assemblages revealed that these relationships were much weaker in croplands compared to grasslands, suggesting a reduced sensitivity of plant assemblages to bioclimatic variations in intensively managed habitats [44].…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, high trait variance suggests species' abilities to finely tune these traits to specific microhabitats 81 or respond to localised variations in resource availability 82 , contributing to the community's ecological diversity and resilience 83,84 within the Mediterranean ecosystems.…”
Section: Variation Of Plant Functional Traits Across Latitudinal and ...mentioning
confidence: 99%
“…For plants, this Special Issue demonstrates that many studies and large initiatives have addressed this gap since then. A total of 15 contributions used fine‐grain plant community data to address macroecological questions at various extents: global (Kusumoto et al, 2021; Testolin et al, 2021), across the whole Palaearctic (Biurrun et al, 2021; Dembicz et al, 2021; Zhang et al, 2021), across Europe (Axmanová et al, 2021; Boonman et al, 2021; Padullés Cubino et al, 2021; Sporbert et al, 2021; Večera et al, 2021), larger parts of Europe (Cao Pinna et al, 2021; Wagner et al, 2021) or at state level (Bourgeois et al, 2021; Craven et al, 2021). Most of these studies rely on two large vegetation‐plot databases established and maintained by two working groups of the International Association for Vegetation Science (IAVS), the European Vegetation Archive (EVA; Chytrý et al, 2016) by the European Vegetation Survey (Axmanová et al, 2021; Boonman et al, 2021; Cao Pinna et al, 2021; Padullés Cubino et al, 2021; Sporbert et al, 2021; Večera et al, 2021; Wagner et al, 2021) and the GrassPlot database (Dengler et al, 2018) by the Eurasian Dry Grassland Group (Biurrun et al, 2021; Dembicz et al, 2021; Zhang et al, 2021).…”
Section: Contributions In the Special Issuementioning
confidence: 99%
“…Most of these studies rely on two large vegetation‐plot databases established and maintained by two working groups of the International Association for Vegetation Science (IAVS), the European Vegetation Archive (EVA; Chytrý et al, 2016) by the European Vegetation Survey (Axmanová et al, 2021; Boonman et al, 2021; Cao Pinna et al, 2021; Padullés Cubino et al, 2021; Sporbert et al, 2021; Večera et al, 2021; Wagner et al, 2021) and the GrassPlot database (Dengler et al, 2018) by the Eurasian Dry Grassland Group (Biurrun et al, 2021; Dembicz et al, 2021; Zhang et al, 2021). Testolin et al (2021) used data from the global vegetation‐plot database sPlot (Bruelheide et al, 2019), and four relied on regional data compilations (Bourgeois et al, 2021; Craven et al, 2021; Kusumoto et al, 2021; Tordoni et al, 2021). This pattern highlights that community efforts of collating extensive collaborative vegetation‐plot databases, such as EVA, sPlot and GrassPlot, have the potential to facilitate new research avenues (Bruelheide et al, 2019; Dengler et al, 2011; Wiser, 2016), often beyond the initial scopes imagined by the founders of these databases, not mentioning the aims of most original field workers.…”
Section: Contributions In the Special Issuementioning
confidence: 99%
See 1 more Smart Citation